Resistensi Dosen Terhadap Perkembangan Teknologi Digital dalam Pembelajaran di Era Pendidikan Modern - Antonio, Lucky; Evi Sondang Pangaribuan; Fendhy Ongko; Mulianto Mulianto; Nurlela Syafrian Oematan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
This research examines faculty resistance to the development of digital technology in education during the modern educational era. The aim of the study is to identify barriers and explore factors contributing to higher education institutions' resistance to the integration of digital technology. This study employs a mixed-methods approach, utilizing surveys to assess faculty attitudes toward digital technology and interviews to provide deeper insights into personal experiences and perceived obstacles. Data were analyzed using thematic analysis to identify common themes and patterns related to resistance among faculty members from various disciplines across different institutions. The innovation of this research lies in its holistic approach, integrating faculty perspectives and institutional policies, as well as professional development and training related to modern learning theories and the application of digital technology in education. The findings emphasize the need for tailored support and training initiatives to enhance skills and confidence in using digital technology, thereby addressing the specific issues and barriers identified by faculty. This integration of technology into teaching is crucial for enhancing effectiveness and improving the learning experiences of students in an increasingly digital era. Keywords: , ,